Prevalence, incidence, and severity associated with viral respiratory tract infections in Colombian adults before the COVID-19 pandemic - Yuli V. Fuentes; Elsa D. Ibáñez-Prada; Cristian C. Serrano-Mayorga; Carlos G. Pfizenmaier; Marcela Cano; Natalia Boada; Paola Rincon; Esteban García-Gallo; Sara Duque; Andrés F. Ocampo; Alirio Bastidas; Sandra Gomez; et al. (Elsevier, 2022)
Background: Acute respiratory illness (ARI) remains the leading cause of global morbidity. Its primary etiology is viral; nevertheless, viral pathogen identification is limited. Clinical information about Latin America's viral etiology, outcomes, and severity is unknown. This study aims to identify the clinical burden of respiratory viral infections, severity, and adult outcomes. Methods: This multicentric, population-based study was conducted through the Health Institute of Bogotá, Colombia, including adult patients diagnosed with ARI between 2013 and 2019. Data collection followed ARI public health surveillance program. Incidence, etiological pathogens, and mortality were calculated. Results: A total of 2304 patients were included in the study. ARI was most frequently reported in 2018 (23.3% [538/2304]). Incidence varies between years, maintaining a range between 3.5 and 8.4. The most frequent clinical diagnosis was pneumonia in 59.1%. Etiological viral detection was obtained in 21.5% of patients [495/2304], principally by Influenza A. Mortality was 21.8%, and ICU admission was 7.3%. The type of event did not predict the causative pathogen, disease severity, or mortality. Conclusions: ARI is a leading cause of morbidity and mortality in Colombia. ARI incidence varies per year and is caused mainly by Influenza A. The classification used in the surveillance program does not correlate with viral etiology, disease severity, and mortality.